Effects of traditional medical herbs "minor bupleurum decoction" on the non-specific immune responses of white shrimp (Litopenaeus vannamei). Issue 64 (May 2017) - Wu, Yu-Sheng; Lee, Meng-Chou; Huang, Cheng-Ting; Kung, Tzu-Chi; Huang, Chih-Yang; Nan, Fan-Hua
Abstract: This study is investigating the effect of minor bupleurum decoction (Xiao-Chai-Hu decoction) on the non-specific immune response of white shrimp ( Litopenaeus vannamei ). To determine prophenoloxidase activity (proPO), reactive oxygen species production (ROS), superoxide anion production (O2 − ), nitric oxide production (NO), phagocytic rate (PR), phagocytic index (PI), superoxide dismutase activity (SOD), total haemocyte count (THC) and differential haemocyte count (DHC). In this experiment, treating with different dosages (0, 0.25, 0.5 and, 1%) of minor bupleurum decoction to detect immune parameters on day 0, 1, 2, 4, 7, 14, 21 and 28. Result is shown that 0.25% treatment significantly enhanced the superoxide dismutase (SOD) activity and, 0.25 and 1% treatment significantly increased the ROS production, nitric oxide (NO) production and phagocytic rate (PR) moreover, 0.5 and 1% treatment induced the proPO activity and superoxide anion (O2 − ) production. Evidence exactly indicated that minor bupleurum decoction is able to enhance the non-specific immunity responses of white shrimp via in vivo examination. Highlights: Minor bupleurum decoction exactly induce the white shrimp non-specific immune response. Minor bupleurum decoction exactly alter the hyaline cell function and ratio. Minor bupleurum decoction is able to enhance the ROS and NO production. Minor bupleurum decoction increase the phagocytic rate.